Chapter Ruth Barcan Marcus on Believing Without a Language - Proust, Joëlle (De Gruyter, 2015)
This paper surveys Ruth Marcus' many contributions to modal logic and its interpretation, starting with her pioneer work on quantified modal logic and ending with the controversies concerning the origin of the idea of rigid reference and other basic ideas in the so-called "New theory of reference." Her contributions are discussed with close attention to who gave credit to whom.